Use of Influenza Antiviral Medications Among Outpatients at High Risk for Influenza-Associated Complications During the 2013–2014 Influenza Season - Havers, Fiona (Clin Infect Dis, 2015)
During the 2013–2014 influenza season, we analyzed data from 6004 outpatients aged ≥6 months with acute respiratory illness (ARI). Among the 2786 ARI patients at higher risk for influenza complications, 835 (30%) presented to care ≤2 days from symptom onset; among those, 126 (15%) were prescribed an antiviral medication.